DISTRIBUTION OF PHOSPHORYLASE IN SOME FISH AND SHELL FISH. - MUKUNDAN, M K; ANTONY, P D (Fishery Technology, 2017)
Phosphorylase content m the muscle of some fish and shell fish were estimated. Jew fish (Johnius duss uneri) and ’sea naran’ (Penaeus indicus) recorded the highest enzyme content among the fish and shell fish studied. As phosphorylase is the key enzyme in glycogenolysis, which is the energy source of fish for muscular activity, the possible role of phosphorylase content as an index of muscular capacity and post-mortem autolysis is discussed.